2016
DOI: 10.1021/acs.est.5b06255
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Method for in Situ Preparation of the MnO2/LaMnO3 Catalyst for the Removal of Toluene

Abstract: MOx/ABO3 is a promising catalyst for the high-efficiency removal of volatile organic compounds. However, this catalyst is limited on practical applications due to its complex synthesis procedure and high cost. In this work, the MnO2/LaMnO3 catalyst was prepared in situ using a facile one-step method for the first time, in which partial La cations were selectively removed from three dimensionally chain-like ordered macroporous (3DOM) LaMnO3 material. After selective removal, the obtained MnO2/LaMnO3 sample expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
135
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 307 publications
(141 citation statements)
references
References 33 publications
6
135
0
Order By: Relevance
“…For instance, Ji et al [9] suggested that the improved catalytic activity of Co-and Febased 3DOM catalysts for toluene oxidation with regards to bulk catalysts could be related to the presence of a higher concentration of adsorbed oxygen species and better low-temperature reducibility, and the same argument has been used by Si et al [10] to explain the high toluene oxidation capacity of 3DOM MnO2/LaMnO3 catalysts. It is well known that the surface properties of pure and ceria-based mixed oxides play a key role in their catalytic performance.…”
Section: Catalytic Oxidation Of Comentioning
confidence: 81%
“…For instance, Ji et al [9] suggested that the improved catalytic activity of Co-and Febased 3DOM catalysts for toluene oxidation with regards to bulk catalysts could be related to the presence of a higher concentration of adsorbed oxygen species and better low-temperature reducibility, and the same argument has been used by Si et al [10] to explain the high toluene oxidation capacity of 3DOM MnO2/LaMnO3 catalysts. It is well known that the surface properties of pure and ceria-based mixed oxides play a key role in their catalytic performance.…”
Section: Catalytic Oxidation Of Comentioning
confidence: 81%
“…[28,29] The perovskite LaMnO 3 indeed showso utstanding catalytic activity for the ORR, butp oor catalytic activityf or the OER. [28,29] The perovskite LaMnO 3 indeed showso utstanding catalytic activity for the ORR, butp oor catalytic activityf or the OER.…”
Section: Introductionmentioning
confidence: 99%
“…The oxideso ft he transition-metal manganese, such as MnO 2 and LaMnO 3 ,a re considered to be superior catalysts for the ORR. [28,29] The perovskite LaMnO 3 indeed showso utstanding catalytic activity for the ORR, butp oor catalytic activityf or the OER. For perovskite-type oxides of manganese,t he high activity is usually ascribed to the averagev alence of Mn 4 + /Mn 3 + , which provides am oderate interaction between the surfaceo ft he catalytic materiala nd intermediates.…”
Section: Introductionmentioning
confidence: 99%
“…The selective removal of A-site cations from the ABO 3 framework in acidic environments has been attributed to the longer length of the AÀO bonds in comparison to the BÀO bonds [40]. It is expected that if the ABO 3 perovskite is terminated with B-site elements, the catalytic activity will be improved [40][41][42][43][44]. The Sr removal and corresponding increased B-site cation coverage has been strongly correlated to the activity [40][41][42][43][44][45][46][47].…”
Section: Introductionmentioning
confidence: 99%
“…It is expected that if the ABO 3 perovskite is terminated with B-site elements, the catalytic activity will be improved [40][41][42][43][44]. The Sr removal and corresponding increased B-site cation coverage has been strongly correlated to the activity [40][41][42][43][44][45][46][47]. For example, Feng et al, used diluted HNO 3 to etch La and Sr away and promote the Mn-rich terminations, which in turn changed the Mn 4 + /Mn 3 + ratio and improve CO oxidation [41].…”
Section: Introductionmentioning
confidence: 99%